Prevalence and Characteristics of Tubectomy Contraceptive Users in Bali from 2019-2020 - Putu Nita Cahyawati (Scopus ID: 57203956416) (Warmadewa University, 2021)
Abstract Indonesia is the country with the largest population in Southeast Asia. The total population in Indonesia was recorded at 255.18 million, with a population growth rate of 3.33 million every year. This population growth has an impact on the economic development and welfare of the country. One of the efforts to suppress the increasing population is to use tubectomy contraception. This study aims to determine the characteristics of tubectomy contraceptive users in Bali in 2019-2020. The design of this research was descriptive cross-sectional. The inclusion criteria in this study were tubectomy contraceptive acceptors recorded in the medical records of the Sanjiwani Hospital in the range of 2019 to 2020. The exclusion criteria were incomplete medical record data. The results of this study found that the prevalence of tubectomy users at the Sanjiwani Hospital from January 2019 to September 2020 was 6.71%. Characteristics of the most users are 36-45 years old, as many as 32 people (65.3%), the highest number of children are 3 children, namely 22 people (44.8%), the highest education level was high school level, which is 24 people (49%), the most occupations are housewives as many as 32 people (65.3%), the most common type of tubectomy was postpartum tubectomy as many as 40 people (81.6%), and for insurance, the most is a Surat Keterangan Tidak Mampu (SKTM) which is as many as 27 people (55,1%). This study concludes that the characteristics of the most contraceptive users are 36-45 years old, the highest number of children are 3 children, the highest education is senior high school, the majority are IRT, the most type of tubectomy contraception is postpartum, and the majority of insurance used is SKTM. Keywords : contraception, tubectomy, RSUD Sanjiwani, Bali